DIABETIC KETOACIDOSIS (DKA) AS AN INITIAL MARKER OF TYPE 1 DIABETES MELLITUS (T1DM) IN CHILDREN (CIPEEX, 2025)
Introduction: Diabetic ketoacidosis (DKA) is the most severe acute metabolic complication of type 1 diabetes mellitus (T1DM) in children, characterized by hyperglycemia, metabolic acidosis, and ketonemia. In many cases, DKA constitutes the initial clinical manifestation of the disease, highlighting delays in diagnosis and failures in the recognition of early signs. The occurrence of DKA at the time of diagnosis is associated with higher risks of morbidity and mortality, prolonged hospitalizations, and possible neurological impacts, representing an important public health and clinical problem. Objective: To analyze diabetic ketoacidosis as an inaugural marker of type 1 diabetes mellitus in children, emphasizing risk factors, clinical characteristics, and prognostic implications. Methodology: This is an integrative literature review, in which the Health Sciences Descriptors (DeCS) “Children,” “Diabetic Ketoacidosis,” and “Type 1 Diabetes Mellitus” were used, combined with the Boolean operator AND, in the Lilacs and PubMed databases. Inclusion criteria for the articles were applied, such as: original studies, published in the last 5 years (2020–2025), and available in English, Portuguese, or Spanish. A total of 42 articles were found, 20 from PubMed and 22 from Lilacs. Of these, 10 texts considered most relevant were selected for the composition of this study. Results: The analysis of the studies revealed that between 30% and 40% of children diagnosed with T1DM present DKA as their first clinical manifestation. The highest incidence is observed in children under 5 years of age, due to the nonspecific nature of symptoms and the difficulty in early recognition of the condition. Factors such as socioeconomic inequality, barriers to accessing health services, and low population knowledge about warning signs contribute to delayed diagnosis. In addition to acute complications, such as the risk of cerebral edema, severe episodes of inaugural DKA have been associated with long-term neurocognitive deficits. Despite its clinical relevance, there is still a shortage of in-depth national studies correlating the occurrence of inaugural DKA with prevention policies and health education strategies. Conclusion: The analysis shows that diabetic ketoacidosis as an initial marker of type 1 diabetes mellitus in children presents patterns similar to those observed in international studies, but with particularities related to access to health services, age at diagnosis, and socioeconomic factors. These findings reinforce the need to intensify health education strategies, expand professional training for early recognition, and structure public policies aimed at reducing the incidence and severity of DKA in the pediatric context.
Keywords: children; diabetic ketoacidosis; type 1 diabetes mellitus